Anticancer chemotherapy through the umbilical vein - Priario, Julio C (Cirugía del Uruguay, 2020)
Regional antineoplastic chemotherapy through the hepatic artery has already been discussed by us in this Society and in the 1965 Uruguayan Congress of Surgery . Now we want to discuss the possibility of doing this therapy via the adult umbilical vein ...